Implementasi Prinsip Usability F-Shape Pattern Pada Konten Website - Jimmy Hendisaro Zebua; Restyandito Dito; Lucia Dwi Krisnawati (Jurnal Informatika, 2012)
Website as a medium of information can not be separated from website content itself. How visitors get the information they want is very dependent on the placement of such information. This research which involve the design and testing of respondents concluded that in general, users tend to read using n “F” pattern , therefore the lay out of the most important content must be placed on both the recommended reading area of the “F” pattern. This research is using the Informatics Engineering’s website as case study and propose a better design to improve the readibility of the information based on “F” pattern. Kata Kunci : Website, F-Pattern, Konten Website, Usability